Comparative efficacy of Bifidobacterium bifidum, Bifidobacterium longum, Bifidobacterium infantis, Lactobacillus rhamnosus composition and prucalopride in treatment of constipation variant of irritable bowel syndrome - V. T. Ivashkin; O. M. Drapkina; A. A. Sheptulin; O. S. Shifrin; Ye. A. Poluektova; S. Yu. Kuchumova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To estimate effect of probiotics and enterokinetic agents on severity of clinical symptoms, presence of bacterial overgrowth syndrome (BOS) and quality of life of patients with constipation variant of irritable bowel syndrome (IBS-C).Material and methods. Comparative analysis of effect of probiotics, enterokinetic agents and placebo on dynamics of main clinical symptoms, intestinal microflora state and quality of life in IBS-C patients was carried out. Investigation of Florasan-D probiotic, composed of Bifidobacterium bifidum, Bifidobacterium longum, Bifidobacterium infantis, Lactobacillus rhamnosus, enterokinetic agent Resolor (prucalopride) and placebo was carried out in 50 patients with IBS-C, conforming Rome III criteria without organic diseases according to results of present investigation. Overall 8 men (16%) and 42 women (84%) with mean age of 35 years [33,7; 41,1 years] were investigated. Patients received probiotic Florasan-D 250 mg bid, placebo — in a similar mode; patients received Resolor 2 mg as a single-dose in the morning. Intensity of abdominal pain and meteorism were estimated by visual analog scale (VAS), stool consistency — by Bristol stool form scale, frequency of defecation — by calculation of number of defecations for every week of treatment. BOS was assessed by lactulose hydrogen breath test, quality of life — by The Short Form-36 (SF-36) questionnaire. Treatment was carried out for 28 days. Results. In the group of IBS-C patients efficacy of Florasan-D probiotic in relation to basic symptoms reduction, improvement of quality of life, normalization of hydrogen breath test scores was comparable to those at Resolor application. Conclusions. Probiotic of Florasan-D and enterokinetic Resolor at application in patients with IBS-C for 4 wks possess similar efficacy in main symptom reduction, relief of BOS, improvement of quality of life. Florasan-D is better tolerated by patients due to gradual increase of stool frequency during treatment course.